1985
DOI: 10.1212/wnl.35.6.834
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Alzheimer's disease and vascular dementias

Abstract: Over 5 years, we followed 199 patients with dementia of the Alzheimer type (DAT), 69 with multi-infarct dementia (MID), and 43 with mixed dementia (MIX). All three diagnostic categories had comparable progression of behavioral and cognitive impairment and need for home care or institutionalization at follow-up. However, 50% survival from diagnosis was 2.6 years for MID and 2.5 years for MIX, compared with 3.4 years for DAT. The 50% survivals from onset were longer than previous reports would suggest (8.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
3
3

Year Published

1986
1986
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(109 citation statements)
references
References 0 publications
7
96
3
3
Order By: Relevance
“…This type of memory is known to be more severely impaired than remote memory in human dementia (12). The present results that rats with permanent 2VO exhibited severe deficit in the learning of new information on the 8-arm radial maze task agree well with our previous data (4) and those reported on the memory loss in normal aged hu- mans and dementia patients (12,13). In this study, we found that daily treatment with TMP from the second day after the learning trial significantly improved this learning deficit.…”
Section: Discussionsupporting
confidence: 93%
“…This type of memory is known to be more severely impaired than remote memory in human dementia (12). The present results that rats with permanent 2VO exhibited severe deficit in the learning of new information on the 8-arm radial maze task agree well with our previous data (4) and those reported on the memory loss in normal aged hu- mans and dementia patients (12,13). In this study, we found that daily treatment with TMP from the second day after the learning trial significantly improved this learning deficit.…”
Section: Discussionsupporting
confidence: 93%
“…3 All patients had a complete medical, neurological, psychiatric, and neuropsychological evaluation, with laboratory work, brain computerized tomography (CT), and EEG to rule out treatable causes of dementia. Of these patients, 84 had a clinical diagnosis of MID based on the presence of typical features 2 and a modified Hachinski score 6 of 2 6.…”
Section: Methodsmentioning
confidence: 99%
“…12 A progressive illness with uniformly poor prognosis, 3 MID may account for approximately 20% of all organic dementias. 4 There is presently no accepted treatment for this disease, but there is some rationale for the prevention of MID via the control of risk factors for stroke and by the prophylactic administration of aspirin to patients at risk.…”
Section: (Stroke 1987;18:138-141)mentioning
confidence: 99%
“…3 Dementia is associated with a high mortality, with a mean survival of approximately seven years from the time of diagnosis in Alzheimer's disease patients. 4 It is also a major cause of impaired QoL. However, the boundary between minimal cognitive impairment and dementia is somewhat arbitrary and difficult to define.…”
Section: Cognitive Impairmentmentioning
confidence: 99%